An Epidemiological Evaluation Of A Typical Mycobacterium And TB/HIV-AIDS Status In Malaysia : Clinical And Microbiological Outcomes Of The Diseases. - Syed Sulaiman, Assoc.Prof Dr Syed Azhar; Ibrahim, Assoc.Prof.Dr Pazilah (2003)
In view of the heterogeneous nature of the epidemiology of tuberculosis, the increasing number of cases associated with AIDS and the spread of resistance to antibiotics, all methods of combating the disease must be mobilized. BCG does not prevent reactivation of latent forms and has no impact on transmission of tuberculosis; it is of great value in preventing the most serious forms, miliary and meningeal tuberculosis'